KAJIAN KRITIS DAMPAK ARSITEKTUR PASCAMODERN PADA PERWUJUDAN TIPOLOGI PERKANTORAN BANGUNAN THE ENERGY JAKARTA - Nugraha Witama, Handy; Saliya, Yuswadi (Jurnal Riset Arsitektur, 2024)
Abstract - The rise of architecture in Indonesia undergoes a significant change caused by the influence and existing developments, so the architecture of the archipelago is fading. Those influences caused the need of architectural critique as an objective learning of architecture design in Indonesia, such as responding to contextual and specific typology function. The Energy is a Postmodern office building that’s located in the SCBD Jakarta. This research critically analyse the impact of Postmodern architecture towards the embodiement of The Energy Building office typology, also criticize the suitability to the context of the SCBD area and the effieciency of energy usage. The research focus on the building's shape, exterior appearance, interior, energy efficiency, zonation, activities. This research uses descriptive, comparative, and normative methods with qualitative approach, the data of the object study is analysed by explanations of Postmodern architectural theory relating to the energy efficiency standards and contextual architectural theory in studying the embodiment of The Energy's office typology on the basis of architectural criticism theory. For data gathering by field observation, interview with the developer on The Energy building and literature study. This critical architecture research is sought to give an impact and understanding of the wider comunity and future architecture planning based on architectural theories. The final study results reveal the impact of Postmodern on the realization of The Energy's office typology from the scope of the study is said to be well and appropriate, and is positively integrated with Contextual, and energy efficiency that affect the comfortability of workers’ and rental price. The embodiment of The Energy's typology also develops and adopts from the previous, by following the development of architectural styles and technology, and the characteristics of the people that reflect the sophistication of the era. The outcome of the study produces conclusions and lessons also generate hypotheses for the future embodiment office typology. Keywords: critical study, Postmodern, office typologie, SCBD Jakarta